2013
DOI: 10.1063/1.4816438
|View full text |Cite
|
Sign up to set email alerts
|

Growth, disorder, and physical properties of ZnSnN2

Abstract: We examine ZnSnN2, a member of the class of materials contemporarily termed “earth-abundant element semiconductors,” with an emphasis on evaluating its suitability for photovoltaic applications. It is predicted to crystallize in an orthorhombic lattice with an energy gap of 2 eV. Instead, using molecular beam epitaxy to deposit high-purity, single crystal as well as highly textured polycrystalline thin films, only a monoclinic structure is observed experimentally. Far from being detrimental, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 28 publications
13
135
5
Order By: Relevance
“…This reduction in band gap is even greater than the approximately 1 eV difference reported by Feldberg et al 15 Similar trends were reported in the comparison of the calculated band gaps and total energies of the ordered and disordered ternary zincblendebased ZnSnP 2 system, with larger band gaps and smaller energies of formation for the two ordered, octet-rulepreserving CuAu and chalcopyrite structures, compared to an ordered octet-rule-violating structure, and to a structure with Sn and Zn atoms placed randomly on the cation sublattice. 44 For the ZnSnN 2 system, the defect calculations by Chen et al 20 also provide some insight, although less directly, into the reductions in band gaps that can be expected from violations of the octet rule.…”
Section: B Results Of First-principles Calculationscontrasting
confidence: 44%
See 4 more Smart Citations
“…This reduction in band gap is even greater than the approximately 1 eV difference reported by Feldberg et al 15 Similar trends were reported in the comparison of the calculated band gaps and total energies of the ordered and disordered ternary zincblendebased ZnSnP 2 system, with larger band gaps and smaller energies of formation for the two ordered, octet-rulepreserving CuAu and chalcopyrite structures, compared to an ordered octet-rule-violating structure, and to a structure with Sn and Zn atoms placed randomly on the cation sublattice. 44 For the ZnSnN 2 system, the defect calculations by Chen et al 20 also provide some insight, although less directly, into the reductions in band gaps that can be expected from violations of the octet rule.…”
Section: B Results Of First-principles Calculationscontrasting
confidence: 44%
“…It was suggested that controlling the degree of this disorder would allow the controlled variation of the band gap from 1 to 2 eV. 15 However, measurement of the band gap by photoluminescence excitation spectroscopy 19 of material that looked wurtzitic in x-ray diffraction gave a gap in close agreement with accurately predictive quasiparticle band structure calculations for perfectly ordered P na2 1 crystals, using experimentally determined lattice parameters. 13,26 The main question we address in this paper is how to reconcile these seemingly contradictory observations.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations